Digitalization: A Step Closer To Sustainability. The Case of Romania And Neighbor Countries From The Perspective of Desi Components - Maria MORARU (Communications of International Proceedings, 2022)
The progress in digital transition of all states of the European Union can be tracked through the Digital Economy and Social Index (DESI) components, which involves the digital competitivity in areas such as human capital, fixed and mobile broadband connectivity, integration done by businesses and digital public services. The overall image of progress made in digitalization area by European Union member states is mixed, leaving a considerable gap between the countries with high levels and lower level of DESI components. Through the study we aim to analyse and compare Romania and fellow countries such as Hungary, Bulgaria and Slovakia to the average European Union DESI components and bring recommendations. The research method applied is comparison for better highlighting of the differences between the countries and european average and pointing out further directions.
Keywords: DESI components; digitization; digital competitivity; e-government; sustainability